1999
DOI: 10.1093/oxfordjournals.aje.a009781
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Calcium, Vitamin D, and Dairy Food Intake to Ischemic Heart Disease Mortality among Postmenopausal Women

Abstract: To investigate whether greater intakes of calcium, vitamin D, or milk products may protect against ischemic heart disease mortality, the authors analyzed data from a prospective cohort study of 34,486 postmenopausal Iowa women 55-69 years old and without a history of ischemic heart disease who completed a dietary questionnaire in 1986. Through 1994, 387 deaths due to ischemic heart disease were documented (International Classification of Diseases, Ninth Revision, codes 410-414, 429.2). The multivariate-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
219
2
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(237 citation statements)
references
References 44 publications
9
219
2
7
Order By: Relevance
“…We found no association between intake of the majority of the dairy products and CHD, a finding consistent with previous literature (15,17,20,23,32,36,37) . For example, in a case-control study of 378 men and 129 women aged 25-79 years, Tavani et al concluded that neither total milk, whole milk, semi-skimmed milk, yoghurt nor cheese was associated with increased CHD risk in men and women (1) .…”
Section: Discussionsupporting
confidence: 93%
“…We found no association between intake of the majority of the dairy products and CHD, a finding consistent with previous literature (15,17,20,23,32,36,37) . For example, in a case-control study of 378 men and 129 women aged 25-79 years, Tavani et al concluded that neither total milk, whole milk, semi-skimmed milk, yoghurt nor cheese was associated with increased CHD risk in men and women (1) .…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the Kuopio observational study, (2) other observational studies have found that calcium intake was inversely associated with ischemic heart disease in elderly women (19) and inversely associated with mortality from stroke but not cardiovascular disease (20) or had no effect. (21) Interventional studies of calcium supplementation have shown beneficial changes to the circulating lipid profile of elderly women, reduced visceral adipose tissue accumulation, transient reductions in blood pressure, and an increased rate of weight loss in obese patients.…”
Section: Discussionmentioning
confidence: 72%
“…Data from a prospective study of 35 000 postmenopausal women set up in 1986 were reported by Bostic et al (1999). Total calcium, and that from milk products was estimated.…”
Section: Resultsmentioning
confidence: 99%
“…A pooled estimate of the odds for a vascular event in the 10 prospective studies, either heart disease or stroke, is 0.84 (0.78-0.90). Total energy intake is an important confounding factor in this context and so a separate pooling was done with the three studies in which adjustment had been made for this (Vijver et al, 1992;Bostic et al, 1999;Elwood et al, 2003). This gave an almost identical estimate, namely 0.85 (0.70-1.03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation